Progress and prospects for research on Martian topographic features and typical landform identification - Liu, Danyang; Cheng, Weiming (Frontiers in Astronomy and Space Sciences, 2023)
The study of Martian surface topography is important for understanding the geological evolution of Mars and revealing the spatial differentiation of the Martian landscape. Identifying typical landform units is a fundamental task when studying the origin and evolution of Mars, which and is of great research significanceprovides important information for landing on and exploringation Mars, as well as estimating the age of the Martian surface and inferring the evolution of the Earth's environment. In this paper, we first investigate Mars exploration, data acquisition and mapping, and the classification methods of Martians landforms classification are introduced. Then, the identification of several typical Martians landform types is shown in detail, including such as wind-sandaeolian landforms, hydromorphic fluvial landforms, and impact landformscraters, is shown in detail. Finally, the prospects of Mars data acquisition, landform mapping, and the construction and identification of the Martians landform classification system are presented. The construction of the Martians landform classification system based on the Earth and Moon landform classification system and the identification of typical Martians landforms using deep learning are important development directions in planetary science research.